Review of Between "Angels and Demons": Trauma in Fictional Representations of Roger Casement, by Mariana Bolfarine and The Literary Afterlives of Roger Casement, by Alison Garden - Angus Mitchell (Review of Irish Studies in Europe)
Review of Between “Angels and Demons”: Trauma in Fictional Representations of Roger Casement, by Mariana Bolfarine (São Paulo: Editora Humanitas, 2019). ISBN 978-85-7732-354-8